Real-time Multi-object Face Recognition Using Content Based Image Retrieval (CBIR) - Muhammad Fachrurrozi; Saparudin Saparudin; Erwin Erwin; Mardiana Mardiana; Clara Fin Badillah; Junia Erlina; Auzan Lazuardi (Institute of Advanced Engineering and Science, 2018)
Face recognition system in real time is divided into three processes, namely feature extraction, clustering, detection, and recognition. Each of these stages uses different methods, Local Binary Pattern (LBP), Agglomerative Hierarchical Clustering (AHC) and Euclidean Distance. Multi-face image search using Content Based Image Retrieval (CBIR) method. CBIR performs image search by image feature itself. Based on real time trial results, the accuracy value obtained is 61.64%.